To simplify the expression \( 6(3q - 4) + 18 - 12q - 7(4q + 5) \), let's follow these steps:
-
Distribute the constants in front of the parentheses: \[ 6(3q) - 6(4) + 18 - 12q - 7(4q) - 7(5) \] This gives us: \[ 18q - 24 + 18 - 12q - 28q - 35 \]
-
Combine like terms:
- For the \(q\) terms: \( 18q - 12q - 28q = (18 - 12 - 28)q = -22q \)
- For the constant terms: \( -24 + 18 - 35 = -24 - 17 = -41 \)
-
Finally, we combine the results: \[ -22q - 41 \]
So, the simplified expression is: \[ \boxed{-22q - 41} \]